PENERAPAN PROJECT BASED LEARNING DALAM MEMBUAT KOLASE PADA ELEMEN DASAR FASHION DESIGN - Dinano Vianingrum; Inty Nahari; Lutfiyah Hidayati; Deny Arifiana (Fakultas Teknik Universitas Negeri Surabaya, 2023)
The Project Based Learning Learning Model is one model that can be applied in making collages on the Basic Elements of Fashion Design. This learning model has great potential to make students work collaboratively in producing work according to the demands of the independent curriculum. The population of this study was students at SMK Dharma Wanita Gresik, Fashion Design Skills. The purpose of this research is to find out how to apply the Project Based Learning learning model to the Basic Elements of Fashion Design in making collages, to find out the results of learning to make collages after applying the Project Based Learning learning model, to find out the level of collaboration of students in making collages through the Project Based Learning learning model. The research was carried out by observing the application of the Project Based Learning learning model, the collaborative level of students, and the assessment of learning outcomes. The application of Project Based Learning and the collaborative behavior of students was assessed by 3 observers through observations during the learning process while learning outcomes were obtained from the assessment of collage products. Data from the application of Project Based Learning gets an average score of 93.45% with very good quality, the collaborative level gets an average score of 93.05% with very good quality, and learning outcomes to make collages get an average score of 88.4. With the application of the Project Based Learning learning model in making collages, it shows that learning can be carried out at a very good collaborative level and learning outcomes achieve a minimum completeness criterion value.